NOVEL PENGAKUAN EKS PARASIT LAJANG KARYA AYU UTAMI: KAJIAN KRITIK SASTRA FEMINIS SOSIALIS - , LINTANG NURLISSYA; , Drs. Rudi Ekasiswanto, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Feminist literary criticism takes women as their main focus. This type of criticism describes the socialist feminism movement brought by writers through works of literature. This writing entitled â Novel Pengakuan Eks Parasit Lajang by Ayu Utami: A Socialist feminism Literary Criticismâ describes the feminist aspects in the novel using the socialist feminism literary criticism. The study of the novel Pengakuan Eks Parasit Lajang (PEPL) can be concluded that there are profeminist characters and also contrafeminist characters in this novel. A profeminist character is a character that is pro to the feminist movement, while on the other hand a contrafeminist character is a character who disagrees with the idea of feminism and the feminist movement. In the novel PEPL, struggle by the female characters against the patriarchal system which is believed to be the root of the gender inequities issues that led women to be in the second class of the society can be found. The feminist ideas in the novel PEPL shows that there are similarities between the novel PEPL and the profeminist characters represented in the novel. These characters struggle to warn the females to be aware and conscious that they are being treated as a second-class in the society of patriarchal system.